2015
DOI: 10.1186/s12998-014-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Foam pads properties and their effects on posturography in participants of different weight

Abstract: BackgroundFoam pads are increasingly used on force platforms during balance assessments in order to produce increased instability thereby permitting the measurement of enhanced posturographic parameters. A variety of foam pads providing different material properties have thus been used, although it is still unclear which characteristics produce the most effective and reliable tests. Furthermore, the effects of participant bodyweight on the performance of the foam pads and outcome of the test are unknown. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
5
22
0
1
Order By: Relevance
“…The finding of age-related differences has been confirmed by other investigators [8]. Other investigators have also shown that different types of foam from different manufacturers affect the score [8][9][10][11][12]. Different levels of elasticity and thickness yielded different scores on postural control velocity, torque variances, and other measures.…”
Section: Introductionsupporting
confidence: 55%
“…The finding of age-related differences has been confirmed by other investigators [8]. Other investigators have also shown that different types of foam from different manufacturers affect the score [8][9][10][11][12]. Different levels of elasticity and thickness yielded different scores on postural control velocity, torque variances, and other measures.…”
Section: Introductionsupporting
confidence: 55%
“…33 Researchers have established that standing on the foam pad decreases postural stability by disrupting the reliability of the somatosensory input 34 ; however, because males are likely to have a larger mass than females, the increased deflection of the balance pad could theoretically provide an advantage in the BESS foam conditions, particularly for those weighing more than 90 kg. 35 Lastly, psychological factors, including motivation and attentiveness, may explain sex differences among age cohorts. 21 Males were less attentive and more agitated during postural-stability tasks, which could result in worse performance during balance testing.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al ( 2008a , b ) have suggested that thin rubber of foam enables closer contact with the rigid surface beneath the foam, which allows plantar tactile sensory feedback and ankle movements to be more effective. In addition, the deformation properties of the foam surface matched to the participants’ weight (Gosselin and Fagan, 2015 ). The heavier participants might be in closer contact with surface beneath the foam.…”
Section: Discussionmentioning
confidence: 99%
“…Caution should be taken when using foam pads on force platforms during balance assessments. To evidence a postural control difference in relation to the physical activity status, the postural task difficulty has to be accurately calibrated, since the foam properties (Patel et al, 2008a , b ) and the anthropometric characteristics of the participant (Gosselin and Fagan, 2015 ) may alter posturographic data.…”
Section: Discussionmentioning
confidence: 99%